2013
DOI: 10.1080/15230406.2013.783449
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-view strategies for enhanced understanding of dynamic tourist activity through geovisualization at regional and national scales

Abstract: This article is part of research exploring various ways to visualize the complexity of sentient movement in space and time. In this case, visualization focuses on the movement of tourists on the West Coast of the South Island of New Zealand, with some commentary on national tourist activity. Working at the atomistic level of the individual we adopt space, time, and activity (s,t,a) as the three main dimensions of sentient movement, but we emphasize activity as a privileged dimension where visualization is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…With the increasing availability of accelerometer data and the ease with which locational information can be collected with devices such as Global Positioning System [ 65 ], a time–activity–location diagram will be needed. One solution would be to integrate time geography visualisation approaches [ 40 , 48 , 58 ] with time–activity diagrams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing availability of accelerometer data and the ease with which locational information can be collected with devices such as Global Positioning System [ 65 ], a time–activity–location diagram will be needed. One solution would be to integrate time geography visualisation approaches [ 40 , 48 , 58 ] with time–activity diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…Ringmaps offer an innovative, data-driven, and compact way of visualising space, time and activity in association with their contextual settings [ 48 ]. The ringmap is made up of a geographical map in the centre and surrounding rings.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous techniques are available for spatiotemporal data exploration and below we outline several basic, but effective techniques that are viable for PPL management needs. While new sophisticated 3D geovisualization techniques that present the spatial and temporal movements of tourist (Zhao, Forer, Sun, & Simmons, 2013) have been developed, these type of geovisualizations are most appropriate when tracking a visitors movement within a destination. While reservations capture a single tourist's movement from their home to the destination, these paths are usually not complicated, and may not be worth showing.…”
Section: Utilizing Information Generated From Geographic Data Miningmentioning
confidence: 99%
“…A typical method of visualizing 3D spatiotemporal data is space-time path (STP) analysis. (1)(2)(3) Zhao et al used STP to visualize the movement behavior of tourists visiting New Zealand and analyzed which activities (e.g., sightseeing, vacation, and dining) tourists were performing at staying places. (2) Zhao et al visualized Halifax census tract data according to individual daily movement patterns.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3) Zhao et al used STP to visualize the movement behavior of tourists visiting New Zealand and analyzed which activities (e.g., sightseeing, vacation, and dining) tourists were performing at staying places. (2) Zhao et al visualized Halifax census tract data according to individual daily movement patterns. (1) Ostermann showed that it was possible to trace the movement paths of park visitors and identify places with a high density of activities by using global positioning system (GPS) location information.…”
Section: Introductionmentioning
confidence: 99%